Semiotics: Signs and Meaning in Contemporary Dance in Malaysia - Mumtaz Begum Aboo Backer (Wacana Seni Journal of Arts Discourse, 2007)
Semiotics is the study or signs and their meanings, and is best related to the works or Swiss linguist Ferdinand de Saussure, French historian Michael Foucault and American philosopher Charles Pierce. According to Foucault. semiotics is an ensemble or knowledge and technical skills that enables us to perceive where signs might be, to define what constitutes signs, and to understand the relationship between signs and the laws governing them. For Saussure, semiotics is a science that investigates the life of signs and demonstrates what signs consist of and what laws goveen them (Counsell and Wolf 2001: 19).